The triglyceride and glucose index and risk of nonalcoholic fatty liver disease: A dose–response meta-analysis - Ling, Qin; Chen, Jiawei; Liu, Xiao; Xu, Yi; Ma, Jianyong; Yu, Peng; Zheng, Kai; Liu, Fuwei; Luo, Jun (Frontiers in Endocrinology, 2023)
Background The triglyceride and glucose (TyG) index is associated with the risk of nonalcoholic fatty liver disease (NAFLD), but the dose−response relationship between them is still unknown. We conducted a comprehensive meta-analysis to study the dose−response association between the TyG index and the risk of NAFLD. Methods We systematically searched the Cochrane Library, PubMed, and Embase databases until July 2022 for relevant studies. The robust error meta-regression method was used to investigate the dose−response association between the TyG index and NAFLD. Summary relative risks (ORs) and 95% CIs were estimated by using a random-effects model. Results A total of 4 cohort and 8 cross-sectional studies were included, with 28,788 NAFLD cases among the 105,365 participants. A positive association for the risk of NAFLD was observed for each additional unit of the TyG index with a linear association (p=0.82), and the summary OR was 2.84 (95% CI, 2.01-4.01). In the subgroup analyses, a stronger association of the TyG index with NAFLD was shown in females than in males (men: OR=2.97, 95% CI 2.55-3.46, women: OR=4.80, 95% CI 3.90-5.90, Psubgroup<0.001). Conclusion The TyG index may be a novel independent risk factor for NAFLD beyond traditional risk factors. Systematic Review Registration https://www.crd.york.ac.uk/prospero, identifier (CRD42022347813).